Structural determination, by cryo-EM, of the hemocyanin from the mollusk Concholepas concholepas with substantial biomedical impact - Ellena, Matías Nahuel (2023)
The single-particle cryo-electron microscopy (cryo-EM) advances since the Resolution Revolution has allowed the study of a wide range of proteins that were impossible to analyze with such precision with previous techniques and resolution. The recent acquisition of a Titan Krios microscope in Brazil is a remarkable achievement that positions the country as a leader in cryo-EM in Latin America. However, training researchers across the region is essential to optimize and maximize this technology. Collaborative efforts between Chilean and Brazilian research groups can promote widespread access to this methodology, fostering regional scientific development using state-of-the-art techniques. Here, we present a synergistic approach to determine the cryo-EM structure of Concholepas concholepas hemocyanin (CCH), an oxygen-transporting mega-dalton oligomer found in many invertebrates. Hemocyanins are employed as natural immunostimulants with significant biomedical and clinical applications. Understanding their precise molecular mechanisms is essential for targeted improvement. Structural diversity among homologous hemocyanins, particularly regarding glycosylation patterns, might account for their varying efficiency in generating suitable adjuvant effects in immunotherapy. In preclinical studies, Chilean researchers have shown that CCH holds promise for biomedical applications due to its superior stability, solubility, and immunological response induction. However, its structure and amino acid sequence remain unexplored. This collaboration enabled the elucidation of the structure of the CCH, a heterodidecamer with 8 MDa, and D5 symmetry, presenting two distinct monomers called CCHA and CCHB distributed equally along forming a protein with 366 Å height and 316 Å diameter, for the external collar, and almost 60 glycosylation sites distributed internally and externally, that have application for biomedical properties.